Orange Life Jackets: Materiality and Narration in Lesvos, One Year after the Eruption of the “Refugee Crisis” - Tyrikos-Ergas, George (Journal of Contemporary Archaeology, 2017)
During summer 2015 more than 500.000 refugees reached the shore of the island of Lesvos, Greece, seeking a safe passage to Europe. Refugees were travelling packed into plastic dinghies by smugglers. They all wore life-jackets that were discarded upon arrival. This article discusses the way these life-jackets were used both by locals and widely in Europe, through their materiality, as symbolic material of two distinct and conflicting representations of the refugees and the refugee issue.